Inflammasomes: Threat Assessment Organelles of the Innate Immune System - Evavold, Charles L. (Immunity, 2019)
Inflammasomes are supramolecular organizing centers that operate to drive interleukin-1 (IL-1) dependent inflammation. Depending on context, inflammatory caspases act upstream or downstream of inflammasome assembly, serving as the principal enzymes that control activities of these organelles. In this Review, we discuss mechanisms of inflammasome assembly and signaling. We posit that upstream regulatory proteins, classically known as pattern recognition receptors, operate to assess infectious and non-infectious threats to the host. Threat assessment is achieved through two general strategies: (1) direct binding of receptors to microbial or host-derived ligands in the cytosol or (2) indirect detection of changes in cellular homeostasis. Upon activation, these upstream regulatory factors seed the assembly of inflammasomes, leading to IL-1 family cytokine release from living (hyperactive) or dead (pyroptotic) cells. The molecular and physiological consequences of these distinct cell fate decisions are discussed.